Tradition and innovation in the ancient Near East : proceedings of the 57th Rencontre Assyriologique Internationale at Rome 4-8 July 2011 - Archi, Alfonso; Bremanti, Armando (Eisenbrauns, 2015)
In July, 2011, the International Association for Assyriology met in Rome, Italy, for 5 days to deliver and listen to papers on the theme "Tradition and Innovation in the Ancient Near East". This volume, the proceedings of the conference, contains more than 40 of the papers read at the 57th annual Rencontre, including 3 plenary lectures/papers, many papers directly connected with the theme, as well as a workshop on parents and children. The papers covered every period of Mesopotamian history, from the third millennium through the end of the first millennium B.C.E. The attendees were warmly hosted by faculty and students from the Università di Roma "La Sapienza".